2022
DOI: 10.3389/fpls.2022.957735
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nitric oxide promotes salinity tolerance in plants: A meta-analysis

Abstract: Nitric oxide (NO) has received much attention since it can boost plant defense mechanisms, and plenty of studies have shown that exogenous NO improves salinity tolerance in plants. However, because of the wide range of experimental settings, it is difficult to assess the administration of optimal dosages, frequency, timing, and method of application and the overall favorable effects of NO on growth and yield improvements. Therefore, we conducted a meta-analysis to reveal the exact physiological and biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 166 publications
0
4
0
Order By: Relevance
“…These antimitotic agents are widely reported and comparatively evaluated in literature for their efficiency in inducing chromosome doubling through in vitro and in vivo regeneration of varying plant species [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. As indicated in Figure 1 , the influence of these chemicals on the formation of more than one haploid genome in a single cell nucleus of plants occurs as a result of the interference with kinetochore-microtubule attachments or what is widely known as microtubule depolymerization which is also extensively reported [ 18 , 19 , 23 , 24 ].…”
Section: Role Of Autopolyploidy On Legume Response To Salinity Stressmentioning
confidence: 99%
“…These antimitotic agents are widely reported and comparatively evaluated in literature for their efficiency in inducing chromosome doubling through in vitro and in vivo regeneration of varying plant species [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. As indicated in Figure 1 , the influence of these chemicals on the formation of more than one haploid genome in a single cell nucleus of plants occurs as a result of the interference with kinetochore-microtubule attachments or what is widely known as microtubule depolymerization which is also extensively reported [ 18 , 19 , 23 , 24 ].…”
Section: Role Of Autopolyploidy On Legume Response To Salinity Stressmentioning
confidence: 99%
“…Salinity-induced osmotic stress causes water scarcity in plants and leads to a reduction in plant growth. Further, salinity also cause ionic toxicity and nutritional imbalance, therefore resulting in a significant reduction in plant growth. Salinity stress negatively affects plant physiological processes including photosynthesis, nutrient acquisition, and water uptake. Photosynthesis is one of the most important processes that provides energy and organic molecules for the growth and development of plants . However, plant photosynthesis is progressively reduced with increasing salinity stress owing to reduced carbon dioxide (CO 2 ) availability, disturbed light harvesting, hindered electron flow, and carbon assimilation .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [24] investigated the effects of melatonin on drought stress in plants by meta-analysis, which showed that the positive effects of melatonin on biomass and chlorophyll were diminished when the concentration range of melatonin was higher than 80-120 µmol L −1 and that the effects of soil application were more pronounced than those of foliar spraying. Tahjib et al [25] similarly used meta-analysis to conclude that the optimal concentration range for nitric oxide to alleviate salt stress (150 mM NaCl) in plants is 0.1-0.2 mM. Exogenous nitric oxide improves plant salt tolerance by alleviating oxidative damage, promoting photosynthesis, and improving ion homeostasis.…”
Section: Introductionmentioning
confidence: 99%